Gastric epithelial cell turnover, mucus production, and healing of gastric ulcers with carbenoxolone. Issue 10 (October 1977) - Domschke, W; Domschke, S; Hagel, J; Demling, L; Croft, D N
Abstract : Nineteen healthy subjects were studied and 17 patients with gastric ulcer before and after ulcer healing with carbenoxolone. Gastric deoxytibonucleic acid (DNA) loss was measured as an index of epithelial cell turnover, and N-acetylneuraminic acid (NANA) content of gastric juice as an index of mucus secretion. In normal subjects there was a negative correlation (p less that 0-025) between gastric DNA loss and NANA secretion; the lower the cell turnover the higher the NANA production. In gastric ulcer patients DNA loss or turnover was significantly (p less than 0-01) higher than normal, and fell significantly (p less than 0-01) after four weeks' treatment with carbenoxolone when 16 of the 17 ulcers had healed. At the same time NANA output increased significantly (p less than 0-01). It is suggested that patients with gastric ulcer lose cells at a high rate, a state of affairs which is returned towards normal by carbenoxolone, thus allowing the epithelial cells to mature within the mucosa and produce more mucus.